Consequence of the tumor‐associated conversion to cyclin D1b - Michael A Augello; Lisa D Berman‐Booty; Richard Carr; Akihiro Yoshida; Jeffry L Dean; Matthew J Schiewer; Felix Y Feng; Scott A Tomlins; Erhe Gao; Walter J Koch; Jeffrey L Benovic; John Alan Diehl; et al. (EMBO Molecular Medicine)
Abstract Clinical evidence suggests that cyclin D1b, a variant of cyclin D1, is associated with tumor progression and poor outcome. However, the underlying molecular basis was unknown. Here, novel models were created to generate a genetic switch from cyclin D1 to cyclin D1b. Extensive analyses uncovered overlapping but non‐redundant functions of cyclin D1b compared to cyclin D1 on developmental phenotypes, and illustrated the importance of the transcriptional regulatory functions of cyclin D1b in vivo. Data obtained identify cyclin D1b as an oncogene, wherein cyclin D1b expression under the endogenous promoter induced cellular transformation and further cooperated with known oncogenes to promote tumor growth in vivo. Further molecular interrogation uncovered unexpected links between cyclin D1b and the DNA damage/PARP1 regulatory networks, which could be exploited to suppress cyclin D1b‐driven tumors. Collectively, these data are the first to define the consequence of cyclin D1b expression on normal cellular function, present evidence for cyclin D1b as an oncogene, and provide pre‐clinical evidence of effective methods to thwart growth of cells dependent upon this oncogenic variant.